Visualization of immune response kinetics in full allogeneic chimeras - Elkin, Gregory (e-Century Publishing Corporation, 2011)
Background: Donor Lymphocyte Infusion (DLI) is a well-recognized tool for augmentation of the anti-leukemia effect after mismatched bone marrow transplantation. Experimental results show, however, that DLI efficacy is strongly dependent on the number of donor hematopoietic cells persisting in recipient after transplantation. It is strong in mixed chimeras and relatively weak in full chimeras (FC) that replace host antigen-presenting cells by donor antigen-presenting cells. In this study we applied a new in vivo cytotoxicity monitoring method for evaluation of the changes in FC anti-host immunity after co-transplantation of donor and host hematopoietic cells together. Method: Full hematopoietic chimeras and naïve control mice were transplanted with a mixture of equivalent numbers of donor and recipient or donor and third party splenocytes labeled by a cell-permeable fluorescent dye CFDA-SE. The animals were sacrificed at various time points, and their splenocyte suspensions were prepared, depleted of red blood cells, stained with allophycocyanin-labeled anti-H2(b) antibodies, and analyzed using fluorescence-activated cell sorting. The immune response was assessed according to the percentage of single positive CFDA-SE(+)/ H2(b-) cells of all CFDA-SE(+) cells. Results: FC grafted with splenocytes from similar FC mixed with splenocytes from naïve host-type or third-party-type mice rejected host cells within 14 days, and third-party cells within 7 days. NK cell depletion in vivo had no influence on host cell rejection kinetics. Co-infusion of host-type splenocytes with splenocytes obtained from naïve donor-type mice resulted in significant acceleration of host cell rejection (10 days). Naïve mice rejected the same amount of allogeneic lymphocytes within 3 days. Conclusions: Proposed method provides a simple and sensitive tool to evaluate in vivo post-transplant cytotoxicity in different experimental settings. The method demonstrates that FC is specifically deficient in their ability to reject host lymphocytes even when antigen-presenting host cells are provided. DLI improve anti-host immune response in FC but can not restore it to the level observed in naïve donor-type mice.